2016
DOI: 10.1890/14-1134.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in marine ecosystems: Peruvian seabirds, anchovy, and oceanographic conditions

Abstract: In fluctuating environments, matching breeding timing to periods of high resource availability is crucial for the fitness of many vertebrate species, and may have major consequences on population health. Yet, our understanding of the proximate environmental cues driving seasonal breeding is limited. This is particularly the case in marine ecosystems, where key environmental factors and prey abundance and availability are seldom quantified. The Northern Humboldt Current System (NHCS) is a highly productive, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
4
33
0
Order By: Relevance
“…The other oceanographic factor that impacted the abundance of seabirds was SST, but this only concerned cormorants and the evidence was not strong. SST is closely related to the strength of the upwelling intensity and biological productivity in the NHCS and Passuni et al (2016) showed that breeding of cormorants mainly stopped when SST are warm. Passuni et al (2016) also suggested that seabirds in the NHCS possibly used SST as an environmental cue to initiate breeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other oceanographic factor that impacted the abundance of seabirds was SST, but this only concerned cormorants and the evidence was not strong. SST is closely related to the strength of the upwelling intensity and biological productivity in the NHCS and Passuni et al (2016) showed that breeding of cormorants mainly stopped when SST are warm. Passuni et al (2016) also suggested that seabirds in the NHCS possibly used SST as an environmental cue to initiate breeding.…”
Section: Discussionmentioning
confidence: 99%
“…SST is closely related to the strength of the upwelling intensity and biological productivity in the NHCS and Passuni et al (2016) showed that breeding of cormorants mainly stopped when SST are warm. Passuni et al (2016) also suggested that seabirds in the NHCS possibly used SST as an environmental cue to initiate breeding. Therefore, we can hypothesize that warm SST negatively impact the breeding propensity of cormorants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, during years of high water, competition with gulls often increases as a result of reduced availability of nesting habitat (Cuthbert et al 2003). Throughout the nonbreeding season, Common Terns follow the distribution and abundance of prey fish (Cabot and Nisbet 2013), and the northwest coast of South America is a hot spot for productivity (Jahncke et al 2004, Capone and Hutchins 2013, Passuni et al 2016. The Peruvian upwelling ecosystem, part of the Humboldt Current System, is one of the most biologically productive marine environments globally (Jahncke et al 2004, Capone andHutchins 2013).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…In the late 1960s to early 1970s, the combination of heavy fishing pressure and 2 ENSO events (1965 and 1972) resulted in the collapse of the anchovy population, which led to major declines in seabird populations (Jahncke et al 2004). In addition to pressures from commercial fishing, changes in sea surface temperatures caused by ENSO events further reduced prey availability by altering the distribution and abundance of fish along the Peruvian coast (Jahncke et al 2004, Devney et al 2009, Passuni et al 2016. Declines in seabird and shorebird populations have been documented in years of extreme ENSO events such as 1982-1983, when populations of Red-necked Phalaropes (Phalaropus lobatus) assumed to be wintering in the region crashed (Nisbet and Veit 2015) and numbers of Common Terns wintering along the southern coast of Peru were substantially below normal (Hughes 1985).…”
Section: Conservation Implicationsmentioning
confidence: 99%